Integrity at Risk: Structural Weaknesses in the EU’s Regulation of the Revolving Door - Szántó, Soma (Pécs journal of international and European law, 2025)
The revolving door phenomenon, essentially describing the transition of public officials into private sector roles, has always been a prevalent, yet underestimated issue in bureaucratic environments such as the European Union’s institutional system. Despite its systemic nature the problem remains insufficiently addressed in the regulatory sense. Following the specific definition of the problematic areas, this article offers a comprehensive legal analysis of the current regulatory framework concerning the revolving door phenomenon, highlighting its shortcomings particularly regarding post-employment restrictions, monitoring mechanisms and sanctioning capacities.